The prepaid electric meter: Rights, relationships and reification in Unguja, Tanzania. (May 2018) - Jacome, Veronica; Ray, Isha
Highlights: We compare user-provider relations in pre- and post-paid electricity systems in Unguja. Prepaid meters may lead low-income users to trade-off debt, dirty fuels and the dark. The reification of prepaid meters protects the utility from customer dissatisfaction. Most users prefer the prepaid meter because it offers security from debt. The lowest-consuming users value the security of service offered by postpaid regimes. Abstract: Sustainable Development Goal 7, with the light bulb and power button as its symbols, in effect promotes the universal right to basic electricity services. Access for all demands both affordability and cost-recovery, and utilities (and donors) increasingly require users to shoulder the greater burden of cost-recovery. We argue that the electricity system is underpinned by a set of relationships among user, provider and the service itself: these relationships are mediated by the meter, the technology of commodification. Using a constant-comparison approach, and based on a year of interviews and document analysis, we compare postpaid and prepaid meter regimes in Unguja, Tanzania. We ask: what difference does the mode of payment make to the (residential) user, the utility, and to the prospects for meeting SDG 7? We find that the prepaid meter becomes reified with its automated monitoring and measurement mechanism, rendering the once-familiar meter reader obsolete, and shutting off the flow of electricity as soon as the customer's "units" have run down. Reification makes the utility more invisible to the customer, who now blames the meter rather than the utility for poor service or high bills. Our interviews reveal broad support for the prepaid meter, however, because economically vulnerable users expressed greater fear of debt than of the dark, and were willing to cede control of their consumption to the new meter. These findings undermine the common accusation of a "culture of nonpayment" in Africa. We also find that prepaid meters may incentivize the partial return to biomass-based fuels when cash is not available – exactly the behavior that universal access to electricity is supposed to prevent. We conclude that, if access to electricity in sub-Saharan Africa becomes entirely contingent on payment prior to use, this is not fully compatible with a commitment to universal basic access.